(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
The current study was carried out to explore the coping strategies adopted by male flood survivors to overcome the damage and loss induced by floods in Punjab and Sindh provinces of Pakistan in the aftermath of 2022 floods. The study also sought to explore the strategies adopted by flood survivors to cope with emotional and psychological challenges posed by flood disaster. As bread earners, male flood survivors are confronted with a plethora of challenges that include but are not limited to, livelihood disruptions and economic instability from the destruction of agricultural land, livestock, and infrastructure. For evaluating coping methods adopted by male flood during disaster cycle viz preparedness, response and recovery, the current study was conducted by using qualitative research design. Data were collected from 48 male victims of floods in the south of Punjab, especially from Dera Ghazi Khan and Rajan Pur districts and from Qamber Shah Dad Kot and Dadu Districts of Sindh Province by conducting in depth interviews. Semi structured interview guide was used as a tool of data collection. Data were collected in native language of the participants which was later on translated into English. Activating social networks, providing financial assistance, and implementing practical measures like fish farming and flood-resistant crops were all identified as effective coping strategies.